Urgensi Penetapan Hakim Atas Permohonan Itsbat Nikah Di PA. Bangkalan Dan PA. Sampang Dalam Perspektif Hukum Keluarga Islam Indonesia - Candra Dalilah (MAQASID, 2023)
Marriage without a marriage certificate will bring many consequences related to the various rights of the wife and the rights of the children who are born, both material and immaterial which should be accepted in the marriage, as well as the rights to the wealth they have throughout the life of the marriage itself, as well as to matters relating to rights relating to third parties. Such a marriage situation will experience problems when dealing with marriage documents as authentic evidence of marriage.In this context, a legal breakthrough in Itsbat Marriage which was never found in Law Number 1 of 1974, was appreciated by the Compilation of Islamic Law (KHI) precisely in the provisions of Article 7 paragraphs (1), (2), (3) and technically formulated by the chapter of guidelines for proceedings in the PA/community, that the rules for ratification of marriage/itsbat marriage, are made based on a marriage which is held based on religion or is not recorded by the authorized VAT. Answering the legal needs of Muslims regarding the ownership of a marriage book, namely for married couples who have been married religiously but whose legal certainty is doubtful in the eyes of the law. Itsbat marriage in question is in this study the ratification of marriage by the Religious Courts according to their respective jurisdictions. The determination of itsbat marriage by the Bangkalan Religious Court and the Sampang Religious Court is very urgent for legal certainty of husband and wife marriages that have not been recorded at the Office of Religious Affairs